Analisis Proses Sertifikasi Halal melalui Bimbingan Lapangan pada UMKM Industri Halal di Kota Kupang - Nurfitri Ramdani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the halal certification process through field guidance activities for Micro, Small, and Medium Enterprises (MSMEs) in the halal industry in Kupang City. The study used a qualitative approach with a descriptive research type. The research subjects consisted of MSMEs, halal product process assistants, and related parties involved in the implementation of halal certification. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was obtained through source triangulation and technical triangulation. The results of the study indicate that the halal certification process for MSMEs in the halal industry in Kupang City is carried out through several stages, starting from socialization, administrative assistance, raw material inspection, production process, and halal certification submission. Field guidance plays a crucial role in helping MSMEs understand halal certification procedures, complete required documents, and ensure compliance with established halal standards. Direct guidance can increase MSMEs’ understanding, readiness, and awareness of the importance of halal certification in improving product quality and consumer trust. However, the research also identified several obstacles, such as limited understanding of administration among business actors, a lack of human resources, and limited production facilities that meet halal standards. Therefore, ongoing support and synergy between the government, halal facilitators, and MSMEs are needed to ensure a more effective and optimal halal certification process.